2022
DOI: 10.1186/s13059-021-02591-w
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic transcriptome risk scores (PTRS) can improve portability of polygenic risk scores across ancestries

Abstract: Background Polygenic risk scores (PRS) are valuable to translate the results of genome-wide association studies (GWAS) into clinical practice. To date, most GWAS have been based on individuals of European-ancestry leading to poor performance in populations of non-European ancestry. Results We introduce the polygenic transcriptome risk score (PTRS), which is based on predicted transcript levels (rather than SNPs), and explore the portability of PTRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 40 publications
0
64
1
Order By: Relevance
“…PTRS are premised on the regulatory nature of most GWAS loci [ Maurano et al, 2012 ] and use genetically regulated gene expression (transcript abundance), in-stead of SNPs as features for prediction. We recently showed that PTRS are useful fortranslating polygenic signals between different human ancestry groups [ Liang et al, 2022 ], supporting the view that the effects of genes on a phenotype are conserved across ancestry groups. In the current project we hypothesized that the relationships between genes and phenotypes are conserved not only between human ancestry groups, but also across species.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…PTRS are premised on the regulatory nature of most GWAS loci [ Maurano et al, 2012 ] and use genetically regulated gene expression (transcript abundance), in-stead of SNPs as features for prediction. We recently showed that PTRS are useful fortranslating polygenic signals between different human ancestry groups [ Liang et al, 2022 ], supporting the view that the effects of genes on a phenotype are conserved across ancestry groups. In the current project we hypothesized that the relationships between genes and phenotypes are conserved not only between human ancestry groups, but also across species.…”
Section: Introductionmentioning
confidence: 79%
“…To test the portability of PTRS across species, we started by calculating the human PTRS weights, as described in Liang et al [ 2022 ]. Using 356,476 UK Biobank unrelated European descent individuals, we fitted an elastic net regression with height as the outcome variable and the imputed gene expression as the predictor (height = ∑ g γ g · T g + ϵ with ϵ , an error term and T g the imputed gene expression in humans).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations